Objectivity and the rule of law - Kramer, Matthew H. (New York, 2007)
What is objectivity? What is the rule of law? Are the operations of legal systems objective? If so, in what ways and to what degrees are they objective? Does anything of importance depend on the objectivity of law? These are some of the principal questions addressed by Matthew H. Kramer in this lucid and wide-ranging study that introduces readers to vital areas of philosophical enquiry. As Kramer shows, objectivity and the rule of law are complicated phenomena, each comprising a number of distinct though overlapping dimensions. Although the connections between objectivity and the rule of law are intimate, they are also densely multi-faceted.
Keywords: Law and ethics